2020
DOI: 10.1111/1365-2656.13266
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in diet–microbe associations across populations of a generalist North American carnivore

Abstract: Generalist species, by definition, exhibit variation in niche attributes that promote survival in changing environments. Increasingly, phenotypes previously associated with a species, particularly those with wide or expanding ranges, are dissolving and compelling greater emphasis on population‐level characteristics. In the present study, we assessed spatial variation in diet characteristics, gut microbiome and associations between these two ecological traits across populations of coyotes Canis latrans. We hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…The inclusion of stable isotopes in future urban-rural diet analyses would fill important information gaps to couple trophic and urban ecology, as these data capture a crucial dimension of niche space at a broader trophic level. Recent work has demonstrated variation in dietary niche and trophic position for urban versus rural coyotes using stable isotopes (Colborn et al, 2020). To conclude, we provide the first quantification of predator diets in a comparative urban versus rural or wildland framework for multiple predator taxa at a global multi-city scale and revealed that urbanization enriches predator diets with carbon but does not inherently relax predation.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The inclusion of stable isotopes in future urban-rural diet analyses would fill important information gaps to couple trophic and urban ecology, as these data capture a crucial dimension of niche space at a broader trophic level. Recent work has demonstrated variation in dietary niche and trophic position for urban versus rural coyotes using stable isotopes (Colborn et al, 2020). To conclude, we provide the first quantification of predator diets in a comparative urban versus rural or wildland framework for multiple predator taxa at a global multi-city scale and revealed that urbanization enriches predator diets with carbon but does not inherently relax predation.…”
Section: Discussionmentioning
confidence: 75%
“…Carbon and nitrogen isotopic ratios present in scat, hair, and vibrissae allow researchers to assess individual heterogeneity in the trophic niche space (Ben-David, & Flaherty, 2012;Colborn et al, 2020). Higher δ 13 C IR reflect consumption of plants with C4 photosynthetic pathways such as corn and sugarcane, which are common in anthropogenic food sources, in contrast to lower values associated with C3 plants found in rural or wildland habitat (Galetti et al, 2016).…”
Section: Predation Consumption Metricsmentioning
confidence: 99%
“…Majority, yielded completion of 10%, and majority plus gold standard < 1% of images. To underscore the importance of considering multiple consensus thresholds, we evaluated results for coyotes ( Canis latrans ) as a case study, given understanding their placement is valuable to wildlife managers, their dynamic role within the carnivore community and are commonly mistaken for other canid species (Prugh et al 2009, Hilton et al 2015, Colborn et al 2020). There were 520 classifications of coyotes by users, of which 265 reached consensus.…”
Section: Resultsmentioning
confidence: 99%
“…To underscore the importance of considering multiple consensus thresholds, we evaluated results for coyotes as a case study, given their dynamic role within the carnivore community and because they are commonly mistaken for other canid species (Prugh et al 2009, Colborn et al 2020). There were 520 classifications of coyotes by users, of which 265 were classified through one of our consensus criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Broadly, geographic isolation of populations can lead to divergence in microbiota over time due to drift and/or local adaptation. While geography has been shown to play a role in shaping the gut microbiome in a number of taxa [19][20][21][22], few studies have looked at these effects in intraspecific island populations. Relative to interspecific comparisons, intraspecific comparisons can be expected to minimize differences in host factors such as physiology, behavior and ecology, and therefore allow better resolution of factors such as host sex and condition, as well as the effects of geography.…”
Section: Introductionmentioning
confidence: 99%